Nurses’ Knowledge on Post Exposure Prophylaxis for Hepatitis B Virus Infection in Tertiary Care Hospital - Sharma, Kalpana; Adhikari, Sabina (Journal of Chitwan Medical College, 2019)
Background: Nurses are most vulnerable group for having Hepatitis B Virus (HBV) infection from blood and body fluids. These infections are preventable if the nurses have proper knowledge regarding Post Exposure Prophylaxis (PEP) for hepatitis B virus infections and utilize the PEP services. This study aimed to find out the nurses’ knowledge on PEP for HBV infection. Methods: A descriptive survey design was carried out among 116 randomly selected nurses working in different wards of tertiary care hospital. Data was collected from July 8th 2018 to 21st July 2018 using pre-tested self-administered questionnaire. Descriptive statistics was used to describe the variables and chi-square test was applied to explore the association between variables. Results: Results of the study revealed that only 22.4% nurses had good, 21.6% had average, and 56.0% had poor knowledge on PEP for HBV. Majority (68.1%) of the nurses knew about the testing of HBsAg serum antigen after exposure. However, few nurses had knowledge on risk percentage of getting infection (29.3%), contact person for risk assessment (33.6%), constituents of PEP (29.9%), and PEP treatment for unvaccinated/incompletely vaccinated nurse in case of positive (38.8%) and negative (34.5%) sources. Moreover, working unit (p=0.037) and working experience (p=0.027) were the significant variables associated with the level of knowledge on PEP. Conclusions: More than half of nurses’ have poor knowledge on PEP for hepatitis B virus. Hence, there is need of regular in-service education and training for nurses on PEP for HBV to enhance their knowledge and to prevent potential infections.